The Sperm Protein Spaca6 is Essential for Fertilization in Zebrafish - Binner, Mirjam I.; Kogan, Anna; Panser, Karin; Schleiffer, Alexander; Deneke, Victoria E.; Pauli, Andrea (Frontiers in Cell and Developmental Biology, 2022)
Fertilization is a key process in all sexually reproducing species, yet the molecular mechanisms that underlie this event remain unclear. To date, only a few proteins have been shown to be essential for sperm-egg binding and fusion in mice, and only some are conserved across vertebrates. One of these conserved, testis-expressed factors is SPACA6, yet its function has not been investigated outside of mammals. Here we show that zebrafish spaca6 encodes for a sperm membrane protein which is essential for fertilization. Zebrafish spaca6 knockout males are sterile. Furthermore, Spaca6-deficient sperm have normal morphology, are motile, and can approach the egg, but fail to bind to the egg and therefore cannot complete fertilization. Interestingly, sperm lacking Spaca6 have decreased levels of another essential and conserved sperm fertility factor, Dcst2, revealing a previously unknown dependence of Dcst2 expression on Spaca6. Together, our results show that zebrafish Spaca6 regulates Dcst2 levels and is required for binding between the sperm membrane and the oolemma. This is in contrast to murine sperm lacking SPACA6, which was reported to be able to bind but unable to fuse with oocytes. These findings demonstrate that Spaca6 is essential for zebrafish fertilization and is a conserved sperm factor in vertebrate reproduction.